Developing a readiness instrument for LPG-to-induction stove transition: A Technoware, Humanware, Infoware, and Orgaware (THIO) approach - Hasna Wahidaturrasyidah Anshori; Retno Wulan Damayanti; Eko Pujiyanto (Journal Industrial Servicess, 2026)
The transition to induction stoves is a strategic effort to support decarbonization and electrification goals. The success of this transition depends not only on policy and infrastructure, but also on technical, social, informational, and institutional readiness. This study aims to develop and validate a readiness assessment instrument based on the Technoware, Humanware, Infoware, and Orgaware (THIO) framework to evaluate the readiness of stakeholders — including household users and institutional actors — in the transition process. A sequential qualitative–quantitative approach was applied, involving a systematic literature review and expert validation to ensure content validity, followed by empirical testing through a survey of 260 respondents. Data were analyzed using Confirmatory Factor Analysis (CFA). The results show that all indicators across the four THIO dimensions are valid and reliable, with factor loadings, composite reliability, and average variance extracted all exceeding the recommended thresholds. The measurement model also achieved a good overall fit. The validated instrument provides a robust and multidimensional tool for assessing readiness for the transition to induction stoves. Practically, it can be immediately utilized by government agencies, energy institutions, and related stakeholders as a diagnostic tool to systematically identify readiness gaps across technical, human, informational, and organizational dimensions, thereby supporting evidence-based prioritization and phased planning of energy transition programs. Overall, this study contributes to strengthening readiness measurement approaches for clean and sustainable energy transitions.